2023
DOI: 10.1002/jid.3776
|View full text |Cite
|
Sign up to set email alerts
|

Local‐level exposure to conflicts and child health: Evidence from Côte d'Ivoire

Abstract: This paper analyses the impact of the 2002–2011 period of instability in Côte d'Ivoire on child health. It uses two rounds of DHS surveys (1998–1999 and 2011–2012) and geo‐referenced data on conflict event locations, which gives more precise estimates of the effects of conflict on child welfare. Regressions using both spatial and temporal variations of conflict events across birth cohorts show a negative association between proximity to conflict events and child height‐for‐age z‐score. The study also suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…In the case of Côte d'Ivoire, Wayoro (2018) has found that armed conflicts have negatively affected children both those born before and after the 2010-2011 postelectoral violence. The evidence collected with the Armed Conflict Location and Event Database, combined with the 2011-2012 Demographic and Health Surveys (DHS) shows important differences between regions with conflict and those without it.…”
Section: Elections Political Violence and Wellbeing In Côte D'lvoirementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Côte d'Ivoire, Wayoro (2018) has found that armed conflicts have negatively affected children both those born before and after the 2010-2011 postelectoral violence. The evidence collected with the Armed Conflict Location and Event Database, combined with the 2011-2012 Demographic and Health Surveys (DHS) shows important differences between regions with conflict and those without it.…”
Section: Elections Political Violence and Wellbeing In Côte D'lvoirementioning
confidence: 99%
“…Finally, the political violence in Côte d'Ivoire that started in 2000 has negatively affected firm performance lowering total factor productivity (Klapper et al, 2013). Because it is the people that are left to live with the legacy of political violence, political leaders addressing these crises have called for a "population-centric approach" (Gilpin, 2014) ensuring that processes used to mitigate the effects of political violence (Wayoro, 2018) are accountable to these people.…”
Section: Elections Political Violence and Wellbeing In Côte D'lvoirementioning
confidence: 99%